Unnötige Regeln - Hentschel, Elke (Linguistik Online, 2002)
This paper argues that among the rules used in foreign language teaching there are often unnecessary ones. These rules offer detailed description of linguistic facts that probably could be learned easier without them. Although "explanatory rules" of this sort might be quite helpful when offered as additional explanations, they can hinder the language learning process when presented as rules to be learned and obeyed ("learning rules"). In order to show the difference between this set of rules more clearly, several examples are given. They belong to the context of German as a foreign language and concern the declension and comparison of the adjective, diminutives, and the passive voice.